2023
DOI: 10.3390/ijms24108899
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Mesenchymal Stem Cells Protect against Renal Ischemia-Reperfusion Injury by Secreting Extracellular Vesicles Loaded with miR-148b-3p That Target Pyruvate Dehydrogenase Kinase 4 to Inhibit Endoplasmic Reticulum Stress at the Reperfusion Stages

Abstract: Renal ischemia-reperfusion (I/R) injury is a leading cause of acute kidney injury (AKI), with high mortality. Recent studies have reported that human umbilical cord mesenchymal stem cells (HucMSCs) play an important role in repairing organ and tissue injuries because of their unique characteristics. However, the potential of HucMSC extracellular vesicles (HucMSC-EVs) to promote the repair of renal tubular cells remains to be explored. This study found that HucMSC-EVs derived from HucMSCs played a protective ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…One recent study showed that renal ischemia for 1 h and reperfusion for 24 h leads to significant renal IR injury 27 . Based on previous studies, we determined that the time point for investigating renal IR injury should be after 1 h of ischemia and then 24 h of reperfusion.…”
Section: Resultsmentioning
confidence: 99%
“…One recent study showed that renal ischemia for 1 h and reperfusion for 24 h leads to significant renal IR injury 27 . Based on previous studies, we determined that the time point for investigating renal IR injury should be after 1 h of ischemia and then 24 h of reperfusion.…”
Section: Resultsmentioning
confidence: 99%